Efeito do exercício físico agudo em intensidade leve e moderada na concentração sérica de fator neurotrófico derivado do cérebro (BDNF) em indivíduos após acidente vascular cerebral (AVC) na fase crônica - Viviane Aparecida Carvalho de Morais (2016)
Stroke (stroke) is the second leading cause of death in the world and in Brazil is the leading cause of death and disability, which generates great economic and social impact. The injury caused by stroke results in death of neurons, which mainly determines the arising of motor and sensory deficiencies. Associated with these deficiencies and the limitation of activities, physical deconditioning is an important post-stroke aspect. Therefore, aerobic exercise is performed in rehabilitation centers and it is described that this modality of physical activity increases the serum concentration of brain-derived neurotrophic factor (BDNF), a neurotrophin important for neuronal survival. However, little is known about the best aerobic exercise parameters to increase BDNF concentration. The aim of this study was to evaluate the viability of the study and the effect of acute physical exercise in mild and moderate intensity on the serum concentration of brain-derived neurotrophic factor (BDNF) in poststroke patients in the chronic phase. One hundred and fifty-one individuals were screened, but only 22 were eligible and agreed to participate in the study. Participants answered a sociodemographic questionnaire and were assessed for functional independence (Modified Rankin Scale, ERM), cognitive function (Mini Mental State Examination, MMSE), depressive symptoms (Hamilton Depression Scale, HAM-D), Fatigue (Fatigue Severity Scale, FSS) and functional capacity (6-minute walking test, 6MWT). The biological material was collected before and after each exercise session and the BDNF concentration was measured by the Enzyme-Linked ImmunoSorbent Assay (ELISA). Of the 22 individuals, only 10 completed all three sessions. Serum concentration of BDNF did not increase after aerobic exercise at mild intensity (p = 0.354) and functional training (p = 0.261), but increased after aerobic exercise at moderate intensity (p = 0.044). Our results reinforce the literature, which indicates that the moderate intensity is indicated to increase the serum concentration of BDNF. Thus, moderate intensity aerobic exercise could be suggested as an intervention strategy in poststroke individuals